1997
DOI: 10.1002/j.1551-8833.1997.tb08245.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced softening: factors influencing DBP precursor removal

Abstract: Bench‐scale tests demonstrate the importance of magnesium hydroxide precipitation and NOM characteristics on precursor removal by softening. Relationships of hardness removal, natural organic matter (NOM) removal, and selected chemical characteristics of NOM were explored, and the implications of the enhanced softening portion of the proposed Disinfectants/Disinfection By‐products Rule were assessed. For most of the nine raw water sources examined, the amount of dissolved organic carbon (DOC) removed (both on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
5
17
0
1
Order By: Relevance
“…While considering the two source waters from the Luan River, higher content of hydrophobic DOM in LW Sum compared with LW Win , the UV 254 is removed more efficiently by coagulation at natural pH and coagulation under softening condition. Which is agreed with the results from Thompson et al [12] that magnesium precipitation effectively remove the hydrophobic fraction of the organic carbon.…”
Section: Comparison Of Enhanced Softening With Pacl For Lw and Ywsupporting
confidence: 83%
See 1 more Smart Citation
“…While considering the two source waters from the Luan River, higher content of hydrophobic DOM in LW Sum compared with LW Win , the UV 254 is removed more efficiently by coagulation at natural pH and coagulation under softening condition. Which is agreed with the results from Thompson et al [12] that magnesium precipitation effectively remove the hydrophobic fraction of the organic carbon.…”
Section: Comparison Of Enhanced Softening With Pacl For Lw and Ywsupporting
confidence: 83%
“…It is found that a small increase in magnesium precipitation results in a significant NOM removal [12]. Systems that remove at least 10 mg/L Mg hardness as CaCO 3 are proposed to exempt from the enhanced softening requirements by the USEPA [1].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these two base fractions also provided relatively high SUVA values (greater than 2 L/mg m). High SUVA was reported to imply high aromatic character [18,19] and therefore this result implied that the aromatic organic compounds were the active precursors of THMs. The HPON fraction, however, also exhibited high level of SUVA but its specific THMFP was rather low.…”
Section: Hpin and Thmfpmentioning
confidence: 90%
“…High SUVA values were known to indicate high molecular weight, hydrophobic and aromatic character components [10][11][12][13]. This simply meant that SUVA was used to suggest the possibility of organic matters to form potentially harmful disinfection byproducts if presented in adequate quantity, and therefore it could be treated as a possible indicator for the formation of disinfection by-products [14].…”
Section: Docmentioning
confidence: 99%